Desenvolvimento e potencial produtivo do maracujazeiro amarelo irrigado com lâminas de água residuária e de poço - Lima Junior, Juarez Cassiano de (2017)
The objective of this research was to evaluate the vegetative development and productivity of yellow passion fruit as well as disposable chemicals in the soil as a function of different levels of crop evapotranspiration replacement, using domestic sewage treated as an alternative water source. The experiment was conducted in the city of Tianguá, state of Ceará. The experimental strategy consisted of three replicates of a split-plot randomized block design. The plots consisted of two water sources (treated sewage effluent and well water) and the subplots received irrigation slides based on 50; 75; 100; 125 and 150% of crop evapotranspiration. The increase in water availability provided increments in plant variables. Basal diameter was influenced by the water source, presenting its highest values in the cases that it was irrigated with domestic sewage treated. On the other hand, a variable number of leaves did not differ significantly on any type of water. The best fitting equation for both variables was the quadratic polynomial equation, for the data of the last evaluation period. The chlorophyll indices do not differ between any of the treatments. The average productivity of yellow passion fruit also did not differ significantly on any of water sources although they behaved differently. On the one hand, the production data obtained with the use of well water were better fit to a quadratic polynomial equation, whereas those obtained with the production of passion fruit with domestic sewage showed a linear behavior. As regards the soil, irrigation with domestic sewage effluent treated did not cause damages to the chemical characteristics. However, if the rainy season of the region presents below-average rainfall, soil washing is necessary in order to maintain tolerable levels of sodicity.